Ball games and nutrition counseling improve postural control in overweight children. Issue 1 (December 2015) - Kuni, Benita; Rühling, Nina; Hegar, Ulrike; Roth, Christina; Schmitt, Holger
Abstract Background Motor skills are impaired in overweight children whose levels of physical activity are low and these children are more likely to sustain lower extremity injuries. The purpose of this study was to analyze prospectively in overweight children the influence of ball games and nutrition counseling on postural control. Methods In all, 46 overweight children (age: 6–12 years, BMI: female: 25.2 ± 3.6 kg/m2, male: 26.2 ± 2.8 kg/m2 (mean value ± standard deviation) were examined prospectively in four randomized groups (ball games, nutrition counseling, ball games and nutrition counseling, and group without intervention) for six months. A one-legged standing test was performed. Results The children demonstrated improved postural control after six months of intervention: mean difference M1-M2 ± standard deviation: 5 ± 6 error points (p < 0.001, T = 4.906), whereas the control group without intervention did not show any significant improvement: 2 ± 8 error points (p = 0.357, T = 0.972). Conclusions Ball games and nutrition counseling have a positive influence on postural control and therefore could help prevent injury. Trial registration ClinicalTrials.gov Identifier:NCT01825174 . Registered April 2, 2013